2007
DOI: 10.1002/jbm.a.31135
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–thioglycolic acid conjugate: An alternative carrier for oral nonviral gene delivery?

Abstract: Regarding safety concerns, nonviral gene delivery vehicles that have the required efficiency and safety for use in human gene therapy are being widely investigated. The aim of this study was to synthesize and evaluate a thiolated chitosan to improve the efficacy of oral gene delivery systems. Thiolated chitosan was synthesized by introducing thioglycolic acid (TGA) to chitosan via amide bond formation mediated by a carbodiimide. Based on this conjugate, nanoparticles with pDNA were generated at pH 4.0 and 5.0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Hence, this promising scaffold was utilised for NP preparation for the purpose of oral controlled delivery of drugs and macromolecules. Thiolated CS-NPs made from thioglycolic acid and CS were first prepared to deliver DNA to the cells via the oral route (109). The DNA thiolated CS-NPs showed significant improvement in transfection rate when compared to DNA encapsulated unmodified CS-NPs.…”
Section: Thiolated Chitosanmentioning
confidence: 99%
“…Hence, this promising scaffold was utilised for NP preparation for the purpose of oral controlled delivery of drugs and macromolecules. Thiolated CS-NPs made from thioglycolic acid and CS were first prepared to deliver DNA to the cells via the oral route (109). The DNA thiolated CS-NPs showed significant improvement in transfection rate when compared to DNA encapsulated unmodified CS-NPs.…”
Section: Thiolated Chitosanmentioning
confidence: 99%
“…Chitosan modified with poly(d,llactide-co-glycolide) (PLGA) nanosphere provided a platform for prolong and sustained intracellular release of nucleic acids [66]. Introduction of thioglycolic acid (TGA) to chitosan improved the efficacy of oral gene delivery systems due to increased stability from nuclease degradation [67]. Thiolated chitosan appeared to possess enhanced mucoadhesiveness and cell penetration, higher gene transfer potential and sustained gene expression [68].…”
Section: Chitosan Derivativesmentioning
confidence: 99%
“…Polyplexes, complexes of DNA and polymer, are one example of delivery systems that offer advantages such as high stability and high transfection efficiencies [56]. Regarding thiolated chitosans, it was demonstrated that the complexation of 102 F. Sarti and A. Bernkop-Schn€ urch chitosan-TGA with pDNA leads to a transfection rate in Caco-2 cells that was fivefold higher than that gained with unmodified chitosan/pDNA [57]. Thiolated chitosan/pDNA complexes were prepared at pH 4.0 and 5.0 and were resistant to degradation during incubation with DNase I for 30 min.…”
Section: Transfection-enhancing Propertiesmentioning
confidence: 99%